Online Learning-Related Visual Function Impairment During and After the COVID-19 Pandemic - Qian Fan; Hongxia Wang; Wenjun Kong; Wei Zhang; Zhouyue Li; Yan Wang (Frontiers Media S.A., 2021)
This study aimed to review the consequences of increased online learning, which was precipitated by the coronavirus disease 2019 (COVID-19), on visual function, as well as the methods for preventing the associated visual impairment. The recent finding implies that a higher incidence of myopia may be observed during the pandemic than that before. The myopia prevalence was 59.35% in COVID-19, which was higher than that in the normal period. COVID-19-related influence of developing myopia among students should be addressed and under control. Online learning precipitated by COVID-19 is likely to increase the global burden of visual function impairment. This review highlighted useful measures to prevent online learning-related visual function impairments, including the following: (1) desktop illumination of no >300 lx, online learning time for primary, and middle-school students of no more than 20-30 min per session; (2) daily video time for preschool children not exceeding 1 h, and for school-age children and adolescents not exceeding 2 h; (3) after every 30-40 min of online learning, moving eyes away from the screen or closed for 10 min; (4) engaging in outdoor activities for ≥ 2 h a day; (5) suitable screen and learning environment settings and correct postures for reading and writing; (6) sufficient sleep and proper nutrition. Preventing online learning-related visual impairment during and after this unprecedented pandemic will facilitate future ophthalmic practice.